Utilizing Local Wisdom-Based Reading Text to Improve Students’ Reading Comprehension of the Second Grade of MAN 1 Baubau - Fikratul Khairiyah; Abidin Pammu; Sukmawaty Sukmawaty (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Local wisdom-based reading text as the authentic teaching material overcomes various obstacles of reading comprehension in EFL which activate the students’ schemata. This research is about utilization of the local wisdom-based reading text to improve students’ reading comprehension. The types of comprehension include identifying main idea, understanding unfamiliar words, identifying text details, and being able to find reference within the text, being able to make inference regarding the text. The research design was pre-experimental study using a sample of 27 students in the second grade of Madrasah Aliyah Negeri 1 Baubau. A pre-test was administrated before intervention and after the same test for the post-test was administered to find out the students’ improvement on reading comprehension. The result confirmed that local wisdom-based reading text is an effective tools to empower EFL learners’ comprehension. The most prevalent improvement regards familiarity of the lexical items ability in making inference as well as finding out main idea. The students’ positive responses that were based on the perception confirmed that local wisdom-based reading text could be encouraged to come up with pedagogical implication applicable for the EFL classroom notably at the second grade of MAN 1 Baubau.